The heart of coaching supervision : working with reflection and self-care - Turner, Eve; Palmer, Stephen, 1955- (Essential coaching skills and knowledge., 2019)
The Heart of Coaching Supervision takes us on a journey that starts with understanding who we are, and why we do what we do the way we do it, so that we can help those we work with understand themselves and their practice. The journey includes our background and personal and professional influences and considers the need for self-resourcing to resource others. It examines our being alongside our doing, to ensure that we can provide the best possible service to all those we work with. The book's highly experienced contributors provide a unique perspective on supervision's benefits. The chapters cover themes that support self-discovery and resourcing including the three Ps of supervision and coaching, diversity and inclusion, resourcing, working with intense emotions and the self as instrument. Nancy Kline's Thinking Environment A is explored in a supervision context alongside creative forms of reflective and expressive writing and resourcing through a peer supervision chain. The Heart of Coaching Supervision also includes ten engaging, international case studies, considering the role of supervision in depth. A key contribution to the field, the book is essential reading for all coaches and mentors, coaching supervisors and psychologists, managers in a coaching role and anyone in a helping profession or leadership position wanting to better understand the wide benefits of supervision.